Class Assessment Card (CAC) for lecture preparation - Kumar, Pranav; Mohd Mokhtar, Sany Sanuri; Al-Swidi, Abdullah Kaid (2013)
A class consists of students from different backgrounds possessing a varied level of knowledge, intelligence, psychology, and interests.When a lecturer enters a new class the first time, he/she needs to understand these factors quickly and rationally in order for him/her to be able to impart a reasonable level of teaching in coherence with the university’s quality criteria.Till now this kind of class assessment was being done through a lecturer’s observation.However, a lecturer is usually required to handle several classes of different levels and as such, it is not always possible to remember the quality and learning standards of these classes precisely.Hence, a lecturer who is just depending on observations to prepare the lectures and delivers them in a class which many a times seek to ignore the students with lower level of intelligence or knowledge.The aim of this study therefore, was to develop a model for assessing a class’s learning standards in overall terms using the grounded theory approach.‘No student should be knowingly/unknowingly ignored’ was the starting point of this research. After analyzing several aspects of a class and a lecturer, this study came up with a model consisting of two parts: 1.Class Assessment Card (CAC) for assessing the intellect and receptiveness capabilities of a class which a lecturer can just fill in the first two classes itself through his observations; 2.CAC Evaluation Scheme which offers suggestions to the lecturers as to how to strategize for different types of classes consisting of varying levels of student’s learning capabilities.